2022
DOI: 10.1111/bcp.15515
|View full text |Cite
|
Sign up to set email alerts
|

Examining nonadherence in the treatment of tuberculosis: The patterns that lead to failure

Abstract: Aims Adherence has been shown to be a major predictor of tuberculosis treatment failure and relapse. The current adherence metrics can be improved to provide higher resolution of adherence patterns and identify patients in need of alternative treatment interventions. We investigated how adherence patterns affect treatment outcomes, when adherence is likely to decrease during treatment and which patients are at risk of being nonadherent. Methods Individual‐level data were pooled from 3 clinical trials (n = 3724… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…Other patterns of adherence, such as the timing of missed doses, may be important. 34,35 Third, adherence was dichotomized (100% vs <100% of doses received) before being included in the models used to predict adherence and outcomes. It is plausible that utilizing a continuous functional form of adherence may improve the ability of the more sophisticated methods to eliminate bias due to treatment non-adherence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other patterns of adherence, such as the timing of missed doses, may be important. 34,35 Third, adherence was dichotomized (100% vs <100% of doses received) before being included in the models used to predict adherence and outcomes. It is plausible that utilizing a continuous functional form of adherence may improve the ability of the more sophisticated methods to eliminate bias due to treatment non-adherence.…”
Section: Discussionmentioning
confidence: 99%
“…Second, we calculated adherence using the overall percentage of prescribed doses received. Other patterns of adherence, such as the timing of missed doses, may be important 34,35 . Third, adherence was dichotomized (100% vs <100% of doses received) before being included in the models used to predict adherence and outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The critical role of suboptimal adherence in treatment failure and the development of antimicrobial resistance is perhaps nowhere more evident than in the management of tuberculosis. Fox et al 15 provide insight into the relationship between medication‐taking patterns, the predictors of suboptimal adherence and treatment outcomes in a cohort of subjects ( n = 3724) with tuberculosis. It was reported that missing only 4 clustered treatment days in 1 month increased the risk of treatment failure or relapse by 61%.…”
Section: Figurementioning
confidence: 99%
“…As above, the cross-sectional nature of the oxypurinol plasma concentration data will limit the ability to detect longitudinal adherence behaviour and the use of plasma concentrations will be confounded by the white coat effect, the tendency of patients to change their medication-taking behaviour prior to a clinic visit.The critical role of suboptimal adherence in treatment failure and the development of antimicrobial resistance is perhaps nowhere more evident than in the management of tuberculosis. Fox et al15 provide insight into the relationship between medication-taking patterns, the predictors of suboptimal adherence and treatment outcomes in a cohort of subjects (n = 3724) with tuberculosis. It was reported that missing only 4 clustered treatment days in 1 month increased the risk of treatment failure or relapse by 61%.…”
mentioning
confidence: 99%
“…Not all antibiotic escape mutations are successful and multiple resistance mutations associated with a single drug have been reported [Trauner 2017]. This accumulation of mutations may be an indicator for a "fragile" regimen [Fox 2022] where the concentration / number of active of drugs is insufficient to prevent the accumulation of resistance mutations. Furthermore the particular spectrum of mutations seen might indicate the key drug(s) where selective pressure is being most strongly applied to the mycobacteria by the chosen regimen.…”
Section: Introductionmentioning
confidence: 99%